2019
DOI: 10.1021/acsami.9b01068
|View full text |Cite
|
Sign up to set email alerts
|

Surface Amino Group Regulation and Structural Engineering of Graphitic Carbon Nitride with Enhanced Photocatalytic Activity by Ultrafast Ammonia Plasma Immersion Modification

Abstract: Surface amino group regulation and structural engineering of graphitic carbon nitride (g-CN) for better catalytic activity have increasingly become a focus of academia and industry. In this work, the ammonia plasma produced by a microwave surface wave plasma generator was developed as a facile source to achieve fast, controllable surface modification, and structural engineering of g-CN by ultrafast plasma treatment in minutes, thus enhancing photocatalytic performance of g-CN. The morphology, surface hydrophil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…13 Therefore, several strategies have been developed to enhance the photocatalytic performance of g-C 3 N 4 , such as porous structure design, metal or nonmetal element doping, surface modification, coupling with semiconductors, and so forth. 14 16 …”
Section: Introductionmentioning
confidence: 99%
“…13 Therefore, several strategies have been developed to enhance the photocatalytic performance of g-C 3 N 4 , such as porous structure design, metal or nonmetal element doping, surface modification, coupling with semiconductors, and so forth. 14 16 …”
Section: Introductionmentioning
confidence: 99%
“…These amine groups also act as a shallow electron donor whose free electron lone pairs also effectively and additionally contributed to the reduction of H + to H 2 as seen under the Computational Procedure section. 19,52 Here, more electron density is transferred to the CB of MDY from the −NH x groups as the Fermi level of the amine group is believed to lie above (more negative than) the CB of g-C 3 N 4.7 based on our current band structure experiment and reported electronic structure of liquid ammonia 53 and amine-doped graphene, 54,55 and as shown in Figure 4e (from DFT). Similar characteristics are seen in the electronic band structure of the NH 3 molecule adsorbed (ex situ doping) on a Si nanowire host material, which yields ntype doping, where the Fermi level of NH 3 found pinned near the CB of the host material.…”
Section: ■ Experimental Sectionmentioning
confidence: 70%
“…This surface modification results in g-C 3 N 4 materials with enriched amino groups, extended light-harvesting edges, and electron transport ability, conferring good photoelectric and photocatalytic activity and selectivity. [93] Zhu et al [94] demonstrated, through DFT calculations, that CO 2 molecules preferably adsorb on the two-coordinated nitrogen atoms. Thus, nitrogen- Doping is an interesting approach to tune the electronic structure of semiconductors.…”
Section: Graphitic Carbon Nitride Catalystsmentioning
confidence: 99%